A Case of Ischemic Stroke Complicated by Hemorrhagic Transformation in Rheumatic Heart Disease - Gupta, Kanika; Bankad, Parvati N.; Mohapatra, Bishnupriya; Jain, Gaurav (Journal of Neuroanaesthesiology and Critical Care, 2025)
We report the case of a 57-year-old male with rheumatic heart disease and chronic hepatitis B, who presented with acute left middle cerebral artery infarct and was thrombolysed with tenecteplase. He subsequently developed hemorrhagic transformation with mass effect. As prothrombin complex concentrate could not be arranged, he was managed with cryoprecipitate, tranexamic acid, and vitamin K. He underwent emergency decompressive craniectomy, followed by hematoma expansion requiring a second surgery. Intraoperatively, he had labile vitals requiring vasopressor support and rate control. Despite transient postoperative improvement, the patient suffered cardiac arrest on day 5. This case highlights the complex interplay of thrombolysis, valvular pathology, and clinical decision-making challenges in the management of hemorrhagic transformation in patients with rheumatic heart disease.
Keywords: tenecteplase; ischemic stroke; hemorrhagic transformation; valvular disease